2019
DOI: 10.5334/tohm.513
|View full text |Cite
|
Sign up to set email alerts
|

Slow Orthostatic Tremor: Review of the Current Evidence

Abstract: Background: Orthostatic tremor (OT) is defined as tremor in the legs and trunk evoked during standing. While the classical description is tremor of ≥13 Hz, slower frequencies are recognized. There is disagreement as to whether the latter represents a slow variant of classical OT, or different tremor disorder(s) given frequent coexistent neurological disease. Methods: A systematic literature search of PubMed was performed in February 2019 for "slow orthostatic tremor" and related terms which generated 573 abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
(101 reference statements)
0
14
0
Order By: Relevance
“…Generally, a regular high frequency (13-18 Hz) was the main characteristic of OT, such as primary OT, but low-frequency OT (< 13 Hz) was defined as slow OT (pseudo-OT) [3,4]. Slow OT is mostly associated with neurological diseases, such as ET, dystonia, and parkinsonism [19], and systemic diseases (e.g., multiple sclerosis, paraneoplastic syndrome, thiamine deficiency, Graves' disease) [14][15][16]20]. In addition, delayed-onset slow OT after head trauma and slow OT caused by structural lesions of the brain, such as pontine structures and left dorsolateral midbrain, were also reported [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, a regular high frequency (13-18 Hz) was the main characteristic of OT, such as primary OT, but low-frequency OT (< 13 Hz) was defined as slow OT (pseudo-OT) [3,4]. Slow OT is mostly associated with neurological diseases, such as ET, dystonia, and parkinsonism [19], and systemic diseases (e.g., multiple sclerosis, paraneoplastic syndrome, thiamine deficiency, Graves' disease) [14][15][16]20]. In addition, delayed-onset slow OT after head trauma and slow OT caused by structural lesions of the brain, such as pontine structures and left dorsolateral midbrain, were also reported [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, OT symptoms remained relatively unchanged, but in 6 of 41 cases (15%), the condition gradually progressed over time [17]. Hassan et al [19] reported that multiple medication trials were performed in 98 of 184 OT cases (53.3%). Among the medications tested, clonazepam was most effective, and betablockers, anticonvulsants, and carbidopa-levodopa had a mild benefit in regard to symptoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the journal, Hassan and Caviness reviewed the controversial topic of slow orthostatic tremor (OT). 1 Based on their review of the relevant literature, Hassan and Caviness concluded that “multiple lines of evidence separate slow OT from classical OT,” but they also noted that “clinical and electrophysiologic overlap may occur.” We were invited to discuss the significance of this overlap within the context of tremor classification.…”
mentioning
confidence: 99%
“…The fairly routine performance of electrophysiological tests in patients with orthostatic shakiness has led to the discovery of slow OT and orthostatic myoclonus, which also have been reviewed by Hassan and Caviness. 1,17,18 Tremor frequency and coherence are only two of many measures that could prove useful in the characterization of other tremor syndromes. For example, tremor rhythmicity and frequency stability may be useful in distinguishing Parkinson tremor from essential tremor, 19 and many other electrophysiologic properties of tremor are being explored for their utility in tremor classification.…”
mentioning
confidence: 99%